Pemanfaatan Bakera Pada Ibu Nifas Di Wilayah Kerja Puskesmas Taratara - Vebriannty Buka; Melky Pangemanan; Lucyana L Pongoh (STIKES Columbia Asia Medan, 2025)
Traditional Bakera treatment or a kind of traditional spa is a treatment carried out by postpartum mothers, all traditional Bakera treatment methods use herbal plants. The purpose of this study was to determine how to utilize bakera in postpartum mothers in the Taratara Health Center work area. The type of research used was descriptive qualitative research, with informants consisting of 2 postpartum mothers, 1 village head, and 1 health worker domiciled in Taratara village. The results of the study through in-depth interviews with researchers with 4 informants showed that traditional Bakera treatment has benefits for the healing process of postpartum mothers such as helping to smooth blood circulation, removing toxins that are not needed by the body, accelerating the healing of external wounds after giving birth, helping to warm the body, accelerating the healing of internal wounds, helping to remove dirty blood after giving birth, facilitating breast milk production, increasing appetite, and facilitating the digestive tract.